Level up! Refreshing parental mediation theory for our digital media landscape - JIOW, Hee Jhee (Institutional Knowledge at Singapore Management University, 2017)
This article argues that parental mediation theory is rooted in television studies and mustbe refined to accommodate the fast-changing media landscape that is populated by com-plex and intensively used media forms such as video games, social media, and mobile apps.Through a study of parental mediation of children’s video game play, we identify the lim-itations of parental mediation theory as applied to current trends in children’s media useand suggest how it can be enhanced. This study seeks to improve parental mediation the-ory’s descriptive and explanatory strength by identifying and outlining the specific activitiesthat parents undertake as they impose their media strategies. We explain how restrictive,co-use, and active mediation are constituted by gatekeeping, discursive, diversionary, andinvestigative activities.